Problematic Issues in Conducting Expert Examinations for the Calculation of Key Financial Indicators of Business Entities - Ye. M. Andrushchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article examines methodological and practical aspects of analyzing and calculating the key financial indicators (ratios) of business entities. It analyzes the specific features of the methodology for their calculation as presented in current methodological documents approved at the ministerial level. The primary focus is on problematic issues that may arise for expert economists when conducting research related to the calculation of key financial indicators, the most significant of which is the impact of current legislation on the calculation algorithm itself.